An integrative research framework for enabling transformative adaptation. Issue 68 (February 2017) - Colloff, Matthew J.; Martín-López, Berta; Lavorel, Sandra; Locatelli, Bruno; Gorddard, Russell; Longaretti, Pierre-Yves; Walters, Gretchen; van Kerkhoff, Lorrae; Wyborn, Carina; Coreau, Audrey; Wise, Russell M.; Dunlop, Michael; et al.
Highlights: Transformative approaches will be needed to address adaptation to global change. Transformative approaches require new ways to make decisions about adaptation. The TARA approach (Transformative Adaptation Research Alliance) does this. Abstract: Transformative adaptation will be increasingly important to effectively address the impacts of climate change and other global drivers on social-ecological systems. Enabling transformative adaptation requires new ways to evaluate and adaptively manage trade-offs between maintaining desirable aspects of current social-ecological systems and adapting to major biophysical changes to those systems. We outline such an approach, based on three elements developed by the Transformative Adaptation Research Alliance (TARA): (1) the benefits of adaptation services ; that sub-set of ecosystem services that help people adapt to environmental change; (2) The values-rules-knowledge perspective ( vrk ) for identifying those aspects of societal decision-making contexts that enable or constrain adaptation and (3) the adaptation pathways approach for implementing adaptation, that builds on and integrates adaptation services and the vrk perspective. Together, these elements provide a future-oriented approach to evaluation and use of ecosystem services, a dynamic, grounded understanding of governance and decision-making and a logical, sequential approach that connects decisions over time. The TARA approach represents a means for achieving changes in institutions and governance needed to support transformative adaptation.